MEETING THE CHALLENGES OF ACCESSIBILITY FOR SCIENCE INCLUSIVE CLASSROOMS IN INDONESIAN BASIC EDUCATION SYSTEM - Jamil Suprihatiningrum (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
There is no one-size-fits-all answer to support the uniqueness of a student’s learning needs. Providing accessibility to enable every student to achieve the same learning goals is a critical issue to create an inclusive environment. This study investigated ways of science teachers met the challenges in providing accessibility for students in learning science. Ten participants from three Schools Providing Inclusive Education (SPIE): Schools Cerdas, Pintar, and Pandai in basic education level in the Province of Daerah Istimewa Yogyakarta Indonesia were selected purposively. The participants were interviewed individually and in group to share their thought and experiences in meeting the challenges of learning accessibility for students with disabilities (SWD) in the science classrooms. As part of a qualitative case study, data were analyzed systematically and three themes were generated to discuss the findings, i.e., inclusive pedagogy, inclusive content, and inclusive technology. All participants considered how learning is achieved and provided the means to help students succeed. A syllabus was made available in all schools, although expectations were set low and learning objectives were not clearly defined and measurable. Collaborative teaching only existed in School Pandai with limited co-planning time. All teachers revisited science content and ensured it was set up for all students to meet their expectations. Science teachers in School Pandai created different worksheets based on the student’s needs as the main learning source, while other teachers in Schools Cerdas and Pintar claimed they had no time to vary science modalities. Although all teachers understood how SWD needs to interact with different tools, only teachers in School Pintar and Pandai utilized assistive technologies to help SWD in learning science.